Evaluation of the biological activity of the extracts from Acer negundo and Robinia pseudoacacia leaves on germinating seeds of test cultures - Yurchenko, Eugene; Yakhnovets, Мaksim (Journal of the Belarusian State University. Ecology, 2023)
Ash-leaved maple and black locust belong to the most actively spreading woody invasive species in flora of Belarus. In process of control of these plants by mechanical destruction, a potential use of their phytomass as mulch in gardening is considered. For such usage, the negative allelopathic effect of the phytomass on other plants should be assessed. In the paper the effects of the complex of unidentified biologically active substances from Acer negundo and Robinia pseudoacacia are studied. This is achieved by a method of biotesting: seeds of Lepidium sativum, Raphanus sativus, and Daucus carota were incubated in vitro with water extracts from green leaves of Acer negundo and Robinia pseudoacacia, grounded into powder before extraction. The percent of germinated seeds, length of main root, and length of hypocotylus were recorded. The experimental concentrations of phytomass for extracts were 5, 10, 50, and 100 g/l; distilled water was in control. Two variants of phytomass were tested: green leaves, dried on sun, and green leaves, exposed to rain, but dried on sun beforesuch exposing. The results show that A. negundo has higher allelopathic (phytotoxic) activity, than R. pseudoacacia. In particular, extract from maple (100 g/l) completely suppressed seed germination of all three test plants, whereas extract from black locust (100 g/l) had statistically neutral effect (slightly decreased the percent of germinated seeds) on radish and carrot. As a rule, the inhibitory effect on all three studied parameters of germlings become higher along with increase of extract concentration. Exceptions were the growth of main root in carrot, which was slightly stimulated by extracts from maple (10 g/l) and black locust (50 g/l). The leaf mass of both species after exposing to rain partly lost its inhibitory allelopathic activity. The phytomass of A. negundo after such exposition demonstrated 2.3 times less inhibition effect on growth of roots in watercress (extract 10 g/l). In some cases the phytomass, exposed to rain, had stimulating action on germlings: extract from maple (5 g/l) increased the percentage of germinated seeds in carrot on 25 %; extract from black locust (5 g/l) provoked 1.9 times elongation of root in carrot in comparison with control; extracts from black locust (5–50 g/l) stimulated 1.3–1.4 times elongation of hypocotylus in watercress. Test plants showed different sensitivity to the same extracts. In particular, black locust extract (100 g/l) decreased the number of germinated seeds for watercress to 3.8 %, but only to 89.3 % for carrot. Black locust extract (leaves, exposed to rain, 100 g/l) decreased the average root length in watercress in 4.5 times, but in radish – in 1.5 times.
Keywords: allelopathy; biotesting; invasive species; vegetable cultures; water extract; wooden weeds